Participation of The Armed Forces in The Development of Borders and Border Integration in Per - Jimenez P, Gaspar (2020)
The Armed Forces (FFAA) in Peru are constituted by the Army, the Navy and the Air Force whose primary purpose is to guarantee the independence, sovereignty and territorial integrity of the Republic and, at the same time, assume control of the internal order and participate in the economic and social development of the country according to law. In this sense, the purpose of this research was to determine the participation of the Armed Forces (FFAA) of Peru in the development of borders and border integration - 2017. Through the qualitative methodology, the context and the processes derived from the need for the participation of the Armed Forces of Peru in the development of borders and border integration, applying a systematic procedure constituted the grounded theory, phenomenology, case studies, documentary analysis, content analysis and action research. Finally, it was concluded that the Armed Forces of Peru has the capacity to participate in the development of borders and border integration in the legal framework of the 1933 Constitution, the National Security and Defense Policy and the Framework Law for border development and integration N ° 29778 in force, through the planning and execution of social programs in accordance with the need of the considered borders.